Double trouble: a case of von Recklinghausen’s disease with coexistent lepromatous leprosy - Karthikeyan, Kaliaperumal; Latchoumibady, Kaliaperumal; Sowmya, Srinivasan (The Journal of Infection in Developing Countries, 2011)
Leprosy (or Hansen disease) is a tropical disease which affects the skin and nerves leading to deformities and disabilities. Von Recklinghausen's disease (neurofibromatosis 1) is a well-recognized genetic disorder with both cutaneous and systemic manifestations. Lesions of neurofibromatosis may be mistaken for nodules of lepromatous leprosy and vice versa. Occurrence of both von Recklinghausen's disease and lepromatous leprosy together is very rare. Since cutaneous nodules can also occur in neurofibromatosis, lepromatous leprosy can be easily missed. The presence of lepromatous leprosy in a patient with von Recklinghausen's disease is unique and poses certain diagnostic dilemmas which are discussed in this report.